Managing diversity and equality in the workplace - Angel Sharma (Taylor & Francis Group, 2016)
This paper investigates the relationship of performance appraisals, sociocultural issues, affirmative action (AA), and organizational capabilities in managing diversity and equality in the workplace. Firstly, performance appraisals were found to be a major source of discrimination especially due to raters influence on the actual process. Sociocultural issues had major role as some managers went out of their way in helping their subordinates, especially in paternalistic countries, whereas some left it to workers themselves. AA was laid out to ensure that organizations meet statutory requirements but it often came down to managerial commitments. Finally, this paper found that organizations have to develop capabilities so as to encourage diversity and equality in the workplace.